Implikasi Hukum Pendewasaan Anak yang Melakukan Perkawinan di Bawah Umur dalam Perjanjian Perkawinan - Aristias, Adinda; Fadilla, Dea Aora; Wibowo, Hanifah Fairuz; Manullang, Imelda Arthameisia; Putri, Nasywa Awalia; Ramadhani, Dwi Aryanti (Media Hukum Indonesia (MHI), 2024)
Underage marriage is a phenomenon that still occurs frequently in various countries, including Indonesia, even though there are regulations that regulate the minimum age limit for marriage. This article aims to analyze the legal implications of maturing children who marry underage, especially in the context of marriage agreements. The Marriage Law has stipulated the age limit for marriage (material requirements), one of which is the provisions regarding the minimum age limit which are regulated in Article 14 paragraph (2) of Law Number 1 of 1974. Maturity status is related to the validity of a legal act. Immature legal subjects are seen as legal subjects who are not yet capable of acting for and for themselves before the law. The research method used is a normative juridical approach with analysis of statutory regulations, legal doctrine and relevant concrete cases. The research results show that children who marry underage have limited legal capacity to make legal and binding marriage agreements. Children's immaturity causes vulnerability in understanding and bearing the legal consequences of the agreements made. In addition, marriage agreements involving minors often do not meet the requirements for the validity of a contract under civil law, which means the agreement can be considered null and void. In the case of making a marriage agreement before a notary, especially before a minor is married, it is necessary to guarantee the recognition of the child's maturity status.